Triage strategies in cervical cancer detection in Mexico: methods of the FRIDA Study - Leticia Torres-Ibarra (Salud Pública de México, 2016)
Objective. This paper describes the study design and base- line characteristics of the study population, including the first 30 829 women who enrolled in the Forwarding Research for Improved Detection and Access for Cervical Cancer Screening and Triage (FRIDA Study). This is a large population based study that is evaluating the performance and cost-effective-ness of different triage strategies for high-risk HPV (hrHPV) positive women in Mexico. Materials and methods. The target population is more than 100 000 women aged 30 to 64 years who attend the Cervical Cancer Screening Program in 100 health centers in the state of Tlaxcala, Mexico. Since August 2013, all women in the region have been invited to enroll in the study. The study participants are evaluated to determine hrHPV infection using the Cobas 4800 HPV test. The HPV-16/18 genotyping and cytology triage strategies are performed as reflex tests in all hrHPV-positive participants. Women with a positive HPV-16/18 test and/or abnormal cytology (atypical squamous cells of undetermined significance or worse, ASCUS+) are referred for colposcopy evaluation, where a minimum of four biopsies and an endocervical sample are systematically collected. Histologic confirmation is performed by a standardized panel of pathologists. Results. Among the 30 829 women who have been screened, the overall prevalence of hrHPV is 11.0%. The overall prevalence of HPV16 and HPV18 are 1.5% and 0.7%, respectively. Cytological abnormalities (ASCUS+) were detected in 11.8% of the hrHPV-positive women. A total of 27.0% (920/3,401) of the hrHPV-positive women were referred to colposcopy because of a positive HPV16/18 test and/or abnormal reflex cytology, (31.6% had only ASCUS+, 53.6% were HPV16/18 positive with a normal cytology result, and 9.5% were positive to both triage tests). Conclusion. The results of this study will help policy makers and health service providers establish the best practices for triage in cervical cancer screening in Mexico and other countries. DOI: http://dx.doi.org/10.21149/spm.v58i2.7789